Optimizing Local Regulations in Creating a Balance of Human Health and Environmental Preservation - Maulana Andinata Dalimunthe; Abdi Mubarak Syam; Aris Suhendar; Aulia Rahma Ritonga (Academic Solution Publisher, 2024)
This study aims to analyze the optimization of local regulations on No Smoking Areas (KTR) in creating a balance between human health and environmental preservation in North Labuhanbatu Regency. The research employs a qualitative approach with data collection techniques including observation, interviews, and documentation studies. The research informants consist of the health department, local government, active smokers, and non-smoking communities. The findings indicate that the implementation of the local regulation on KTR has not been effective. This ineffectiveness is reflected in the widespread presence of cigarette advertisements in public areas, the high prevalence of smokers, and the increase in respiratory disease cases after the regulation was enacted. Although the local government has made optimization efforts through the installation of no-smoking stickers and banners, its implementation still faces several challenges, including limited supervision, low public awareness, resistance from the tobacco industry, and weak coordination among stakeholders. Therefore, an integrated strategy based on supervision, education, law enforcement, and technological innovation is required to enhance the effectiveness of KTR implementation.